Utilization of cassava peel waste as an organic fertilizer to build a sustainable cassava production center - Sulistyowati, Lilik; Pangaribuan, Nurmala; Idrus, Olivia; Rachman, Ace (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
The cassava production center in Bogor City is produced by Ciluar Village. Based on the potential of Ciluar Village, which has a lot of cassava agricultural land, cassava peel waste has the potential to be used as organic fertilizer. The aims of this paper are (1) to find out the minimum time to produce compost with the basic ingredients of cassava peels and goat manure with pH parameters according to Indonesian National Standard (SNI) standard; (2) to find out the best composition between cassava skin and goat manure to produce compost. There were three types of treatment based on weight composition comparison between cassava skin and goat manure. The results of the compost quality test were analyzed (statistical test) using analysis of variance (ANOVA) and LSD test (Lessest Significant Difference) to determine the effect of treatment on the observed variables with the help of IBM SPSS 26 software. The conclusions of this study include: (1) the minimum time to produce compost made from cassava peels and goat manure with pH parameters according to SNI is 42 days; (2) the best composition between cassava skin and goat manure to produce compost is a ratio of 7:3.